Metabolismo de carboidratos e de lipídeos durante o exercício na intensidade do limiar ventilatório e o período de recuperação de mulheres obesas - Souza, Cristiane Pereira de (2008)
The inability to oxidize fat is a key factor in the etiology of obesity. However, improved performance and VO2max resulting from physical training leads to increased rates of oxidation of fats. Although, there is still a lack of information about the intensity of exercise can interfere with metabolism of carbohydrates and lipids in obese women during a session of exercise and its recovery, because only in an experimental study there is a negative relationship of obesity on the reinstatement of power after a year. Therefore, this study aims to assess the behavior of the metabolism of carbohydrates and lipids in moderately obese women on a test of acute exercise effects on the intensity of ventilatory threshold and the recovery period, in the stage of pre-and post-training physical. This study had the participation of seven women slightly obese (BMI=4.03 kg/m2), with an average age of 43.0 ± 4.0 years, 163 ± 0.2±33.59 cm and previously sedentary who were submitted to the ergospirometry acute test before and after 16 weeks of training in the intensity of ventilatory threshold. During the test respiratory quotient was evaluated to determine the fats and carbohydrates oxidation during exercise and recovery period. The results found that the volunteers used predominantly the energy that comes from carbohydrates during the session of exercise (67.64% and 69.35% of the total spent provided pre-and post-training, respectively). During recovery the percentage of the fats contribution increase of (46.52% of the total oxidized) to the total energy generated, which discreetly marked with training (53.48% of the total oxidized). Based on the findings was observed that the metabolism of carbohydrates provides the muscle contraction support during the exercise in the intensity of ventilatory threshold and that the recovery period lipid metabolism is the counterpart to repay the body stores energy in obese women.